2019
DOI: 10.1021/acssuschemeng.9b04634
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hexane-Tetrols and -Triols with Fixed Hydroxyl Group Positions and Stereochemistry from Methyl Glycosides over Supported Metal Catalysts

Abstract: Carbohydrates are a renewable feedstock for the production of partially reduced polyols, but typical hydrogenolysis processes are unselective toward C−O bond cleavage at different positions and erase the stereocenters present in the feedstock. In this study, we demonstrate the synthesis of new types of acyclic polyols from methyl glycosides with fixed hydroxyl group positions and stereochemistry. Products include (2R,3S)-1,2,3,6-hexanetetrol, (2R,5S)-1,2,5,6-hexanetetrol, (2S,5S)-1,2,5-hexanetriol, and (4R,5S)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Therefore, the ( S , S )/( S , R ) ratio of tetrol can be tuned through selection of the feedstock TL/EL ratio, catalyst, and temperature, which together determine whether DDM/DDG or DDF are formed during the reaction. We note that the findings in this work concerning the interplay between acid-catalyzed hydrolysis, water-assisted tautomerization, and aldose–ketose isomerization facilitated by background concentrations of OH – are likely relevant to the transformations of other deoxy sugars …”
Section: Resultsmentioning
confidence: 75%
“…Therefore, the ( S , S )/( S , R ) ratio of tetrol can be tuned through selection of the feedstock TL/EL ratio, catalyst, and temperature, which together determine whether DDM/DDG or DDF are formed during the reaction. We note that the findings in this work concerning the interplay between acid-catalyzed hydrolysis, water-assisted tautomerization, and aldose–ketose isomerization facilitated by background concentrations of OH – are likely relevant to the transformations of other deoxy sugars …”
Section: Resultsmentioning
confidence: 75%
“…It was demonstrated that high yields of the target chiral polyols (82-97%) were obtained while maintaining the original chiral structures (92 ≥ 99% ee). 37,39 In addition, they also reported that ReO x -Au/CeO 2 acted as an effective heterogeneous catalyst for the DODH of methyl Scheme 26 DODH of D-glucarate-6,3-lactone with ReO x /ZrO 2 catalyst and stepwise synthesis of dibutyl adipate from D-glucarate-6,3-lactone ReO x /ZrO 2 and Pd/C catalysts. 35 Scheme 27 Transformation of tartaric acid with MoO x /carbon black and HBr.…”
Section: (I) Dodh Of Sugar Alcohols and Cyclic Polyols To Olefins And/ Or Aromatic Compoundsmentioning
confidence: 99%
“…Scheme 30 Transformation of methyl glycosides to the corresponding chiral polyols by DODH, HG, hydrolysis and HG with ReO x -Pd/CeO 2 and hydrogenation catalysts 37,39. Scheme 31 DODH reaction of methyl glycosides with the ReO x -Au/ CeO 2 catalyst 40.…”
mentioning
confidence: 99%
“…1−9 Sugar derivatives have been shown to offer many opportunities to obtain such platform molecules. 10,11 Levoglucosenone (LGO) is a biobased sugar-like compound, which can be produced from cellulose by mild pyrolysis. 12−14 Notably, based on the pyrolytic method developed by the Circa Group, an actual 1000 ton LGO/year plant is currently being developed in France.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Channeling the production of commodity chemicals from petroleum-derived resources to renewable lignocellulosic feedstocks is a great route to the effective transitioning of the chemical industry toward materials and products with a lower CO 2 footprint. Biomass-derived monomers can be used as important platform molecules for the synthesis of polymers, resins, solvents, surfactants, among others. Sugar derivatives have been shown to offer many opportunities to obtain such platform molecules. , Levoglucosenone (LGO) is a biobased sugar-like compound, which can be produced from cellulose by mild pyrolysis. Notably, based on the pyrolytic method developed by the Circa Group, an actual 1000 ton LGO/year plant is currently being developed in France . LGO can also be produced at yields up to 51% using polar aprotic solvents and sulfuric acid at 170–230 °C .…”
Section: Introductionmentioning
confidence: 99%